Adenoma metanéfrico atípico: Reporte de un caso pediátrico - Nakandakari, Mayron D. (2025)
Metanephric adenoma (MA) is an extremely rare type of renal tumor in pediatrics. We report the case of a two-year-old girl with a history of recurrent urinary tract infections. An ultrasound was initially performed, revealing a mass in the left kidney. On CT scan, it was classified as a probable Wilms tumor (WT). She received chemotherapy under the UMBRELLA SIOP-RTSG 2016 Protocol for four weeks. A control CT scan showed no reduction in tumor volume. A radical nephrectomy with retroperitoneal lymphadenectomy was performed. Immunohistochemistry was positive for WT1 and PanCK, and negative for CK7 and AMACR. The Ki67 was heterogeneous. The pathology report concluded atypical metanephric adenoma. She was placed on regular follow-up and was disease-free during the first year of monitoring. In conclusion, not every pediatric renal tumor is a WT, nor is every tumor malignant. Although MA is rare in pediatrics, it should not be ruled out, even in its atypical pathological presentation.